Mechanical and fracture properties of particleboard (Fracture and Structural Integrity, 2018)
Particleboard (PB) are wood-based composites with fine wood fibers bound together by a small amount of polymeric adhesive, widely used in furniture industry and civil engineering. PB plates can be painted, laminated or veneered, and have good dimensional stability and load bearing capacity when properly designed. However, the deformation and fracture of such elements create malfunctions of structures mad of MDF. This paper presents experimental results obtained for three point bending (TPB) tests, mode I and mode II fracture toughness. The bending tests were carried on rectangular specimens, while the fracture toughness tests were performed on Single Edge Notched Bend (SENB) specimen for mode I, respectively on Compact Shear (CS) specimens for mode II loading. Digital Image Correlation techique allow the determination of Crack Relative Displacement Factor and estimation of Energy Release Rate.
Keywords: Particleboard; Fracture Toughness; Digital Image Correlation